Collective Bargaining and the Evolution of Wage Inequality in Italy - Francesco Devicienti; Bernardo Fanfani; Agata Maida (Institute for the Study of Labor (IZA), 2016)
In this paper we study the evolution of the Italian wage inequality, and of its determinants, using two decades of matched employer-employee data covering the entire population of private-sector workers and firms in the Veneto region. We find that wage inequality has increased since the mid-1980s at a relatively fast pace, and we decompose this trend by means of wage regression models that account for both worker and firm fixed effects. We show that the observed and unobserved heterogeneity of the workforce has been a major determinant of the overall wage dispersion and of its evolution. Instead, we find that the importance of the dispersion in firm-specific wage policies has declined over time. Finally, we show that the growth in wage dispersion has almost entirely occurred between job titles (livelli di inquadramento) for which a set of minimum wages is bargained at the nation-wide sectoral level. We conclude that, even in the presence of the underlying market forces, trends in wage inequality have been channelled through the rules set by the country's fairly centralized system of industrial relations.
Keywords: J00; J5; J31; J40; 330; wage inequality; collective bargaining; two-way fixed effects; employer-employee data